2010
DOI: 10.1111/j.1475-6773.2010.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the California Nurse Staffing Mandate for Other States

Abstract: Objectives. To determine whether nurse staffing in California hospitals, where state-mandated minimum nurse-to-patient ratios are in effect, differs from two states without legislation and whether those differences are associated with nurse and patient outcomes. Data Sources. Primary survey data from 22,336 hospital staff nurses in California, Pennsylvania, and New Jersey in 2006 and state hospital discharge databases. Study Design. Nurse workloads are compared across the three states and we examine how nurse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
266
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(282 citation statements)
references
References 23 publications
6
266
1
9
Order By: Relevance
“…Similarly Cook et al (2012) found significant improvements in failure to rescue rates but using an instrumental variable regression found no evidence that this was associated with changes in staffing levels. Spetz et al M a n u s c r i p t (Aiken et al, 2010).…”
Section: E F F E C T I V E a P P R O A C H E S F O R I D E N T I F Ymentioning
confidence: 99%
“…Similarly Cook et al (2012) found significant improvements in failure to rescue rates but using an instrumental variable regression found no evidence that this was associated with changes in staffing levels. Spetz et al M a n u s c r i p t (Aiken et al, 2010).…”
Section: E F F E C T I V E a P P R O A C H E S F O R I D E N T I F Ymentioning
confidence: 99%
“…Fourth, organizations need to ensure appropriate staffing levels for both learning opportunities and workloads that are conducive to having time to report. This last recommendation is based on a body of evidence around lower hospital nursing staffing ratios are linked to lower mortality rates and more positive nursing outcomes [37] . Study limitations include that the focus groups were conducted in one health care organization and may not be transferable to other health care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, esto sugiere la necesidad de plantear otras medidas de estructura como el "skill mix" o mezcla de habilidades para la asignación de personal, por cuanto esta medida apunta a denotar la importancia o no que tiene la diferencia en la formación de los enfermero(a)s sobre los resultados en los pacientes. Aiken (9) menciona la poca evidencia en la literatura respecto a la influencia del personal auxiliar de enfermería en los resultados negativos para los pacientes o que aumenten la carga de trabajo de los profesionales, hallazgo similar a lo encontrado en el presente estudio.…”
Section: Discussionunclassified
“…Otro estudio realizado por Aiken (9) , estableció que la REP en California (USA) se encuentra en 2 pacientes para 1 enfermero(a) en las unidades de cuidado intensivo proporción que se cumple en el 85% de las unidades de cuidado intensivo de este estado. En Pennsylvania y New Jersey(5, 8, 10, 17) la REP de 1 enfermero(a) por dos pacientes críticos se cumple en el 61% y 73 % respectivamente.…”
Section: Discussionunclassified
See 1 more Smart Citation